Cryostructuring of Polymeric Systems. 57. Spongy Wide-Porous Cryogels Based on the Proteins of Blood Serum: Preparation, Properties and Application as the Carriers of Peptide Bioregulators - Egor V. Sidorskii; Mikhail S. Krasnov; Viktoria P. Yamskova; Vladimir I. Lozinsky (Gels, 2020)
Wide-pore proteinaceous freeze–thaw spongy gels were synthesized via the cryotropic gelation technique using the bovine blood serum or its diluted solutions as the protein-containing precursors. The feed systems also included the denaturant (urea) and the thiol-reductant (cysteine). The gel-fraction yield decreased and the swelling degree of the walls of macropores in such heterophase matrices increased with decreasing the initial protein concentration. The optimum freezing temperature was found to be within a rather narrow range from −15 to −20 °C. In this case, the average size of the macropores in the resultant cryogels was 90–110 μm. The suitability of such soft wide-pore gel materials for the application as the carriers of peptide bioregulators was demonstrated in the in vitro experiments, when the posterior segments of the Pleurodeles waltl adult newts’ eyes were used as a model biological target. It was shown that a statistically reliable protective effect on the state of the sclera, vascular membrane and retinal pigment epithelium, as well as on the viability of fibroblasts, was inherent in the proteinaceous cryogels loaded with the peptide bioregulator (Viophtan-5™) isolated from the bovine eye sclera.